Processing of frigate mackerel auxis thazard: post-harvest gender roles - Macachor, Corazon P. (2019)
In Danao City, Philippines, processing of tinap-anan, or hot smoked frigate mackerel (Auxis thazard), is the main livelihood of about 30 fish port vendors. This is a tasty foodstuff with a shelf life of three days at ambient temperature and five days if refrigerated. In 2005, research on histamine levels in tinap-anan found that the product, when processed using traditional methods, would be safe for human consumption if properly handled. In June to December 2010, the roles of women and men in the different stages of producing a safe product were studied. The processors were the offspring of the traditional processors. Eighty-two percent of the present processors were female and 18% were male. Women marketed the product through retail stores and direct selling. The men caught the fish, were responsible for assuring quality at sea, and purchased raw materials from fish ports. Men delivered the processed tinap- anan to restaurants outside the fish port while women delivered it to restaurants inside the port.